Command line fundamentals - Vivek N. (Packt Publishing, 2019)
"Learn to work with common developer tools, operating systems, and other helpful technical utilities. The most basic interface to a computer - the command line - remains the most flexible and powerful way of performing and automating various day to day tasks and processing data. Command Line Fundamentals will teach all about how command lines work. You'll begin by exploring the basics and then focus on the most common tooling - namely the bash shell (which is standard on all Linux and iOS systems). Then, you'll explore the traditional UNIX command line programs as implemented by the GNU project. Next, you'll learn how to use redirection and pipelines to assemble these programs to solve complex problems. You'll also complete the course by exploring the basics of shell scripting that let you automate tasks."--Resource description page